Icon based interface design for ATM using direct combination technique / Norhafizah Kamso - Kamso, Norhafizah (2007)
ATM machine has been widely utilized and has improved a lot since its advent and the ubiquitous characteristic it owns provides the convenient to people in making their daily transaction. Despite of its convenience, there is groups of people population such as functional illiterate population that cannot make use the ATM machine due to the text representation that ATM machine uses. Thus, an alternative ATM interface that uses icons that following Direct Combination principles to replace those texts could possibly eradicate this problem. Direct Combination technique combines two or more objects to produce a new object. The technique is used to design icon based ATM interface. The objective of this research are to identify the Direct Combination principles, design the icon based ATM interface and finally demonstrate the designed interface to be used especially by functional illiterate people. The achievement of the objectives are done through review of related literatures to identify the principles of Direct Combination, design the interface based on those principles and the demonstration done using Macromedia Flash MX with Action Script programming language. The product of this research is successfully done and is hoped to assist those functional illiterate people in utilizing the ATM machine. Recommendations for future work of the icon based ATM interface are increasing the choice of transactions to be performed, incorporate animated icons and voice for better assistance.